ANALISIS KERAGAMAN GENETIK AKSESI KEDELAI INTRODUKSI DARI WILAYAH SUBTROPIS BERBASIS MORFOLOGI DAN MOLEKULER - Rerenstradika Tizar Terryana; Nickita Dewi Safina; Suryani Suryani; Kristianto Nugroho; Puji Lestari (BERITA BIOLOGI, 2020)
Genetic diversity information on soybean germplasm will establish the success of soybean breeding program. In the present study, four qualitative morphological traits information collected from Germplasm Resources Information Network (GRIN), United States Department of Agriculture (USDA) database (www.ars-grin.gov) and 10 microsatellite markers were used to analyze the relationship among 45 accessions of subtropical introduced soybean. The morphological characters of introduced soybean accessions contributed to support the result of molecular characterization. The introduced soybean accessions used in this study were diverse based on morphological and molecular characters. Based on principle component analysis, the flower color, pod color, and growth habit contributed most of the total genetic diversity. All introduced accessions were overlap into four quadrants based on principal coordinate analysis. All microsatellite primers showed polymorphism on total accession observed. High allele variation (9–27 alleles) was observed among tested accessions, with an average allele number and Polymorphic Information Content (PIC) value of 20.7 and 0.95 (0.92–0.97), respectively. All microsatellite markers showed PIC value >0.7 indicating that these markers were suitable for soybean diversity studies with high differentiation and with the average value of genetic diversity of 0.95. The phylogenetic analysis revealed that 45 soybean accessions could be divided into two major groups. Soybean accessions belonging to the same area did not always occupy the same group. The results confirmed that both morphology and molecular genetic diversity in a combined way could efficiently evaluate the variation present in different soybean accessions in any breeding program.